2021
DOI: 10.1002/hbm.25757
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the structural–functional connectome of language in glioma‐induced aphasia using nTMS and DTI

Abstract: Glioma-induced aphasia (GIA) is frequently observed in patients with newly diagnosed gliomas. Previous studies showed an impact of gliomas not only on local brain regions but also on the functionality and structure of brain networks. The current study used navigated transcranial magnetic stimulation (nTMS) to localize languagerelated regions and to explore language function at the network level in combination with connectome analysis. Thirty glioma patients without aphasia (NA) and 30 patients with GIA were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…They observed that local (node) efficiency, a measure for communication strength among the first neighbors of a node, was generally reduced in tumor patients and particularly related to memory function in temporal tumors and to information processing speed in frontal tumors. Zhang et al 16 applied navigated transcranial magnetic stimulation (nTMS) and whole-brain deterministic tractography in left-sided tumors and observed a correlation between the average node degree (and other connectome properties) of the left-hemispheric/nTMS-positive networks and the degree of aphasia. A network-level approach was also adopted by Mrah et al, 19 who computed lesion overlap and white matter dysconnectivity scores for several atlas-based functional networks in low-grade glioma.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that local (node) efficiency, a measure for communication strength among the first neighbors of a node, was generally reduced in tumor patients and particularly related to memory function in temporal tumors and to information processing speed in frontal tumors. Zhang et al 16 applied navigated transcranial magnetic stimulation (nTMS) and whole-brain deterministic tractography in left-sided tumors and observed a correlation between the average node degree (and other connectome properties) of the left-hemispheric/nTMS-positive networks and the degree of aphasia. A network-level approach was also adopted by Mrah et al, 19 who computed lesion overlap and white matter dysconnectivity scores for several atlas-based functional networks in low-grade glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Structural–functional coupling describes anatomical support for functional communications across brain regions ( Baum et al, 2020 ; Gu et al, 2021 ). Zhang et al (2021) reported the structural–functional connectome of language in glioma-induced aphasia, and patients with aphasia were without sufficient functional compensation in the supplementary motor area, which was mainly involved in aphasia. Traditionally, correlation analysis was commonly used for the structural connection (SC) and functional connection (FC) strength to obtain a structural–functional coupling matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study aimed to evaluate the global and local properties of function-specific connectomes derived from linguistic mapping with rnTMS in patients with or without aphasia. The results showed that the global interference of gliomas in the distribution and performance of various brain networks leads to the clinical manifestation of different levels of aphasia [ 66 ]. Alterations in the efficiency of various networks between patients with and without aphasia reflect the interaction of different brain regions in the transmission of information, supporting the theory of language function based on the link between dorsal and ventral streams [ 67 ].…”
Section: Rntms Language Mapping: a Promising Approach In Language Neu...mentioning
confidence: 99%